Maximizing Retail Accounting Performance: A Synergy of Technology Assets and User Capability - Michael, Michael; Widjaja, William (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The widespread adoption of Accounting Information Systems (AIS) in Indonesian retail stores underscores its significance in enhancing operational efficiency and effectiveness, as consumer surveys indicate increased shopping ease and efficiency. This study, conducted with a sample of 150 employees from mini-market retail stores in Jakarta, employs a quantitative survey approach with SEM-PLS to examine the impact of technology assets and user capabilities on AIS performance. Results reveal significant effects of technology assets on AIS performance. Proficient user capabilities further enhance AIS performance, moderating the effect of technology assets. Theoretical implications highlight integrating technological knowledge and user skills in AIS design. In contrast, practical implications suggest investing in advanced technology and employee training to optimize AIS benefits, ultimately improving retail operations' efficiency, accuracy, and customer satisfaction. This research offers valuable insights for stakeholders to make informed decisions and address the challenges of intense competition in the retail industry.